Experimental, DFT and docking simulations of the binding of diapocynin to human serum albumin: Induced circular dichroism - Venturini, Diego [UNESP]; Pastrello, Bruna [UNESP]; Zeraik, Maria Luiza [UNESP]; Pauli, Ivani; Andricopulo, Adriano Defini; Silva-Filho, Luiz Carlos [UNESP]; Bolzani, V. S. [UNESP]; Morgon, Nelson Henrique; Da Souza, A. R. [UNESP]; Ximenes, Valdecir Farias [UNESP] (Royal Society of Chemistry (RSC), 2015)
Diapocynin has been regarded as the active principle of apocynin, which is the most used inhibitor of NADPH oxidase. Here we performed a comprehensive study of the interaction of diapocynin with human serum albumin (HSA). We found that diapocynin binds with higher efficacy to site I of HSA and its binding constant (8.5 × 105 mol-1 L) was almost 100-fold higher compared to apocynin. By interacting with this chiral cavity of the protein, diapocynin became a chiral molecule, which was evidenced by its induced circular dichroism spectrum. The axial chirality was theoretically confirmed by searching the most stable conformations adopted by diapocynin using Density Functional Theory (DFT). The four minimum energy conformers, which presented dihedral angles of 58.00° and 302.00° (syn-aS and syn-aR enantiomers pair bearing 2,2′-dihydroxyl groups at the same side) and 132.86° and 227.14° (anti-aS and anti-aR enantiomers pair bearing 2,2′-dihydroxyl groups at opposite sides) were used as initial conformations for the docking simulations. The highest scored docking pose was obtained for site 1 and the dihedral angle was 106.44°, i.e., an anti-aS chiral conformer. In conclusion, diapocynin is a strong ligand of HSA. An unprecedented combination of DFT calculation and docking simulation was used to explain the acquired chirality of diapocynin when bound to HSA.